Women's Language in Anna Karenina movie (2012) (A Sociolinguistic Perspective) - Marsetya, Rezky Bintang, Dr. Maryadi, MA (2016)
This qualitative study aims at 1) identifying the types of women's language in Anna Karenina movie (2012) and 2)explaining the dominant types of women's language in Anna Karenina movie (2012). The object of the study women's language found in Anna Karenina movie. The data of this research are word, phrases, and sentences that containing women's language in Anna Karenina movie (2012). The researcher uses documentation to collect the data then coding the women's language and dominant types of women's language in Anna Karenina movie (2012). The results show that first there are133 data, 30,07% of Lexical Hedges , 1,50% of Tag Question, 7,51% of Rising Intonation on Declarative, 11,27% of intensifier, 22,55% of Hypercorrect Grammar, 10,52% of Superpolite, 3,75% of Avoidance of Strong Swear Word, and 6,01 of Emphatic Stress. On the category of second results is the dominant types of women's language that shows the Lexical Hedges are having highest point of data in 40 or 30,07% of 133 analyzed data, meanwhile the lowest finding in women's language is Tag Questions which are having 2 or 1,50% of 133 analyzed data.